Depressive Symptoms, Self-Esteem and Perceived Parent–Child Relationship in Early Adolescence - Babore, Alessandra; Trumello, Carmen; Candelori, Carla; Paciello, Marinella; Cerniglia, Luca (Frontiers in Psychology, 2016)
Aims: Early adolescence represents a critical developmental period both from a psychological and a psychopathological point of view. During this period, one of the most common disorder that frequently arises is represented by depression, that tends to become chronic and may produce many subsequent psychosocial impairments. The present study aimed to analyse characteristics of depressive symptoms in an Italian sample of early adolescents, and to explore their connections with self-esteem levels and perceived maternal and paternal emotional availability. Methods: 594 adolescents (50% females) with a mean age of 12.11 years (sd = .98) were administered the Children’s Depression Inventory (CDI), the Rosenberg Self-Esteem Scale (RSES), and the maternal and the paternal forms of the Lum Emotional Availability of Parents (LEAP). Results: Findings highlighted a slightly higher level of depressive symptoms in girls than in boys. Regression analysis showed that, as far as predictors of depression, self-esteem was the most relevant one, followed by maternal and paternal emotional availability. Conclusions: Our results strongly suggested to plan intervention programs aimed at monitoring early adolescents’ self-esteem and supporting relationship with both parents, in order to prevent the emergence of depressive symptoms.